Health State Utilities and Quality of Life in Patients with Hepatitis B - Gloria Woo; George Tomlinson; Colina Yim; Les Lilly; George Therapondos; David KH Wong; Wendy Ungar; Thomas R Einarson; Morris Sherman; E Jenny Heathcote; Murray Krahn (Canadian Journal of Gastroenterology)
BACKGROUND: The effect of chronic hepatitis B (CHB) infection on health-related quality of life (HRQoL) and health state utilities has not been well characterized.